2016
DOI: 10.7202/1036966ar
|View full text |Cite
|
Sign up to set email alerts
|

Interactions cognition-émotion et personnalité psychopathique : des trajectoires distinctes vers les comportements antisociaux et violents

Abstract: Les chercheurs ont depuis longtemps reconnu l’hétérogénéité des individus présentant des comportements antisociaux et violents. Or, l’étude de la personnalité psychopathique (ou psychopathie), par l’examen de ses différentes facettes, peut aider à mieux comprendre cette hétérogénéité. Plus particulièrement, la distinction entre les corrélats des traits interpersonnels et affectifs (Facteur 1) et ceux des traits impulsifs et antisociaux (Facteur 2) de la psychopathie suggère l’existence d’au moins deux trajecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The severity of affective or antisocial traits in individuals with psychopathy related to these scales could be a confounding factor in the current analysis (Hare and Neumann, 2006; Verona, 2016). Indeed, previous studies have reported that deficits in attentional processing during emotional perception are linked to the severity of interpersonal affective traits (Sadeh and Verona, 2008; Newman et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of affective or antisocial traits in individuals with psychopathy related to these scales could be a confounding factor in the current analysis (Hare and Neumann, 2006; Verona, 2016). Indeed, previous studies have reported that deficits in attentional processing during emotional perception are linked to the severity of interpersonal affective traits (Sadeh and Verona, 2008; Newman et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among studies with dimensional analysis, Bresin and collaborators (2014), characterized individuals on PCL-R Factor-1 are by a superior monitoring of errors. It is suggested that these characteristics could be practical to pursue some specific behavior related to psychopathy disorder (e.g., manipulate someone or premeditate action (Verona, 2016)). Pasion and collaborators (2016) also describe this ERN modulation in individuals scoring on interpersonal-affective as individual with high social efficiency.…”
Section: Dimension Of Psychopathy ~ Ernmentioning
confidence: 99%